Odčarani svet Boža Voduška - Bernik, France (Primerjalna književnost, 2012)
This article discusses a literary phenomenon that is oriented utterly subjectively in terms of the concept and content, even though as a whole it is not alienated from the given time and space. When it was published, it aroused a number of varied emotional responses. This is also undoubtedly because it was precisely during this time that the author's personal identity was changing and changed.
Keywords: Vodušek, Božo, 1905-1978; slovenska poezija; lirski subjekt; ekspresionizem; Expressionism; ironija; deziluzionizem; nova stvarnost